2021
DOI: 10.3389/fpls.2021.699530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chemotypic Markers in Three Chemotype Categories of Cannabis Using Secondary Metabolites Profiled in Inflorescences, Leaves, Stem Bark, and Roots

Abstract: Previous chemotaxonomic studies of cannabis only focused on tetrahydrocannabinol (THC) dominant strains while excluded the cannabidiol (CBD) dominant strains and intermediate strains (THC ≈ CBD). This study investigated the utility of the full spectrum of secondary metabolites in different plant parts in three cannabis chemotypes (THC dominant, intermediate, and CBD dominant) for chemotaxonomic discrimination. Hierarchical clustering, principal component analysis (PCA), and canonical correlation analysis assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 93 publications
(132 reference statements)
2
16
0
Order By: Relevance
“…Another study on chemotaxonomic discrimination indicated significant chemical differences in three chemotypes, so that CBD dominant varieties had higher amounts of total CBD, while THC dominant varieties had higher total THC, and intermediate varieties were generally equal to or in between those in CBD-dominant and THC-dominant varieties [ 58 ]. They finally showed that chemotype markers (presence or absence of THC and CBD) could be used as chemical fingerprints for quality standardization or variety identification for clinical studies and cannabis product manufacturing [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on chemotaxonomic discrimination indicated significant chemical differences in three chemotypes, so that CBD dominant varieties had higher amounts of total CBD, while THC dominant varieties had higher total THC, and intermediate varieties were generally equal to or in between those in CBD-dominant and THC-dominant varieties [ 58 ]. They finally showed that chemotype markers (presence or absence of THC and CBD) could be used as chemical fingerprints for quality standardization or variety identification for clinical studies and cannabis product manufacturing [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study on chemotaxonomic discrimination indicated significant chemical differences in three chemotypes, so that CBD dominant varieties had higher amounts of total CBD, while THC dominant varieties had higher total THC, and intermediate varieties were generally equal to or in between those in CBD-dominant and THC-dominant varieties [ 58 ]. They finally showed that chemotype markers (presence or absence of THC and CBD) could be used as chemical fingerprints for quality standardization or variety identification for clinical studies and cannabis product manufacturing [ 58 ]. THC and CBD variations among populations of this Iranian collection enabled us to define studied populations as three different groups: Type I (THC/CBD > 1), Type II (THC/CBD ≈ 1), and Type III (THC/CBD < 1) with a prevalence of THC, both THC and CBD in an approximately equal proportions, and CBD, respectively ( Figure 3 a).…”
Section: Discussionmentioning
confidence: 99%
“…When the pastel hair colour turns to 75% light brown or amber, then inflorescences are ready for the harvest with a total CBD peak of 8.73% [ 55 , 56 , 57 ]. However, once the trichome starts looking grey and much of the THC has already degraded to CBN, the harvest time has passed, and the effects of the buds will be sleepy without any psychoactive effects [ 53 , 54 , 55 ].…”
Section: Harvesting Of Cannabismentioning
confidence: 99%
“…However, as McPartland also reported, these vernacular categories are unreliable for distinguishing between different chemotypes and/or cannabis end uses due to extensive cross-breeding and incomplete labelling during hybridisation ( McPartland, 2017 ). In addition, in most classification studies, samples had come from different sources and had been exposed to inconsistent environmental factors during growth phases, postharvest treatment, sample preparation, and extraction procedures during laboratory analysis ( Jin et al, 2020 , 2021a , 2021b ). Jin et al (2021b) recently addressed these drawbacks.…”
Section: Introductionmentioning
confidence: 99%